The Molecular Neurobiology of Twelve Steps Program & Fellowship: Connecting the Dots for Recovery - Blum, Kenneth (J Reward Defic Syndr, 2015)
There are some who suggest that alcoholism and drug abuse are not diseases at all and that they are not consequences of a brain disorder as espoused recently by the American Society of Addiction Medicine (ASAM). Some would argue that addicts can quit on their own and moderate their alcohol and drug intake. When they present to a treatment program or enter the 12 Step Program & Fellowship, many addicts finally achieve complete abstinence. However, when controlled drinking fails, there may be successful alternatives that fit particular groups of individuals. In this expert opinion, we attempt to identify personal differences in recovery, by clarifying the molecular neurobiological basis of each step of the 12 Step Program. We explore the impact that the molecular neurobiological basis of the 12 steps can have on Reward Deficiency Syndrome (RDS) despite addiction risk gene polymorphisms. This exploration has already been accomplished in part by Blum and others in a 2013 Springer Neuroscience Brief. The purpose of this expert opinion is to briefly, outline the molecular neurobiological and genetic links, especially as they relate to the role of epigenetic changes that are possible in individuals who regularly attend AA meetings. It begs the question as to whether “12 steps programs and fellowship” does induce neuroplasticity and continued dopamine D2 receptor proliferation despite carrying hypodopaminergic type polymorphisms such as DRD2 A1 allele. “Like-minded” doctors of ASAM are cognizant that patients in treatment without the “psycho-social-spiritual trio,” may not be obtaining the important benefits afforded by adopting 12-step doctrines. Are we better off with coupling medical assisted treatment (MAT) that favors combining dopamine agonist modalities (DAM) as possible histone-deacetylase activators with the 12 steps followed by a program that embraces either one or the other? While there are many unanswered questions, at least we have reached a time when “science meets recovery,” and in doing so, can further redeem joy in recovery.